The Impact of Large-Scale Migration on Poverty, Expenditures, and Labor Market Outcomes in Nepal - Shrestha, Maheshwor (World Bank, Washington, DC, 2017)
This paper studies the impact of migration on poverty, expenditures, and labor market outcomes in Nepal. Between 2001 and 2011, the share of male working age population abroad more than doubled, mostly due to young men leaving to work in Malaysia and the Persian Gulf countries. The paper studies the impact using instrumental variables as well as difference-in-difference methods. The findings show that increases in migration to Gulf-Malaysia explain 40 percent of the decline in poverty between 2001 and 2011. The estimates of the marginal propensity of consumption show that a $1 increase in remittance income increases consumption by $0.5, with the largest share going to expenditures on food. The paper also finds that migration increases school enrollment of children, particularly of girls. Furthermore, the findings show that large-scale migration in villages improves labor market outcomes for households without a migrant. An increase in village migration rates of 10 percentage points increases wages by 25 percent, and labor force participation by 4 percentage points. The participation effects are driven by increases in female participation in non-farm sectors, and increased male participation in agriculture. The wage effects are driven by higher agricultural wages for all, and higher non-farm wages for females.